In memoriam: Boris P. Sandomirsky (April 30th, 1938 – January 10th, 2018) - Problems of Cryobiology and Cryomedicine, Editorial Board (Problems of Cryobiology and Cryomedicine, 2018)
Probl Cryobiol Cryomed 2018; 28(1): 96